FIGURE 1. Ciona pomponiae. A in Poorly known Ascidiacea collected in the vicinity of the Commander Islands and East Kamchatka, NW Pacific - Sanamyan, Karen; Sanamyan, Nadya (Zenodo, 2007)
FIGURE 1. Ciona pomponiae. A, internal view of antero-dorsal midline (branchial tentacles, prepharyngeal groove, dorsal tubercle, ganglion and anterior part of dorsal lamina); B, rectum and genital papilla; C, gut loop, pharyngeo-epicardiac openings in retropharyngeal groove, dorsal languets; D, body removed from the test. Published as part of Sanamyan, Karen & Sanamyan, Nadya, 2007, Poorly known Ascidiacea collected in the vicinity of the Commander Islands and East Kamchatka, NW Pacific, pp. 55-68 in Zootaxa 1579 (1) on page 57, DOI:10.11646/zootaxa.1579.1.3, http://zenodo.org/record/5097273